Analyzing The Relationship Between Job Satisfaction and Turnover Intentions Among Hospitality Employees in Cape Coast - Gyebi, Priscilla Wendy; Bonsu, Emmanuel Mensah (Universitas Djuanda, 2023)
The hospitality industry has gained much attention following its enormous contributions to economies. The job satisfaction of employees has been remarked to lead to higher productivity in the hospitality industry. This study explored the effects of employees' job satisfaction and their intention to quit. Through a quantitative research approach using regression models and descriptive statistics, the study analyzed 40 questionnaire responses from employees. The analyses revealed a significant negative relationship between job satisfaction and the turnover intention of employees. The results showed that the socio-demographics of respondents are relevant to their job happiness. It was revealed that employees had fair satisfaction with their jobs, although promotion and work conditions barely influenced their satisfaction. Based on these findings, the study recommended further practice and research.